Initial Systems Theoretic Metamodel of Verification Artifacts. (13th September 2022) - Wach, Paul; Beling, Peter; Salado, Alejandro
Abstract: The last decade has seen an increase in calls for theoretical foundations of systems engineering (SE) along with a transformation to a model‐based and digital paradigm. This transformation is expected to facilitate improved verification. In fact, the literature suggests that the increased complexity of modern engineered systems is challenging the feasibility of traditional verification methods and requires new methods to cope with the change. Furthermore, a review of the SE literature suggests limited focus on verification research. Our research leverages systems theory to characterize the relationships between the verification artifacts. Specifically, we use systems theoretic morphisms to characterize the equivalence preservation between system requirements and verification requirements as well as between a system design and verification models. Although in initial form as provided in this article, our metamodel of verification artifacts is expected to contribute to the theoretical foundations of SE.